Prosthetic valve endocarditis. - Mahesh, B; Angelini, G; Caputo, M; Jin, X; Bryan, A (2005)
Prosthetic valve endocarditis is a catastrophic complication of cardiac valve replacement, associated with high mortality rates. Medical treatment is effective in a few instances of endocarditis involving the leaflets alone in bioprostheses. However, accurate diagnosis, better myocardial protection, and improved surgical strategies have led to better survival in patients undergoing surgery after failed conservative therapy. This comprehensive review addresses various issues involved in the management of this complication.